Students' Perception Toward The Use of Deepl as a Machine Translation Tool for English Writing - Gita Ramadhanti; Yanti Sri Rezeki; Surmiyati (PROJECT (Professional Journal of English Education), 2026)
Students faced challenges in translating Indonesian to English for academic writing. DeepL provided a translation solution, leading this study to investigate students' perceptions of using DeepL as a translation tool for writing in English. This mixed-method study examined 117 students (31 males, 86 females) from the English Language Study Program, semester 6 and 8 programs, Universitas Tanjungpura, selected through purposive sampling. Data were collected using validated online questionnaires. Quantitative analysis utilized descriptive statistics and Mann-Whitney U tests, while qualitative data used thematic analysis. The findings showed that students demonstrated high positive perceptions across all dimensions: PEOU (3.92), PU (3.69), ATU (3.75), and BIU (3.62). DeepL was perceived as highly accessible and effective for enhancing writing quality, particularly in contextual vocabulary and grammar improvement, with no significant gender differences emerging (U = 1245.000, Z = -.544, p = 0.587). In conclusion, DeepL was widely accepted by both genders as a translation tool for writing effectively, improving the efficiency and quality of students' writing. The implication was that DeepL showed strong potential for strategic integration in English writing assignments. However, implementation should have emphasized critical evaluation skills and balanced usage to prevent over-dependence while maximizing benefits for writing efficiency and quality improvement.